COLLABORATIVE GUIDANCE MODEL IN HIGHER EDUCATION: IMPROVE THE QUALITY AND PRODUCTIVITY OF STUDENT RESEARCH - Kurniawan, Dwi Agus; Asrial, Asrial; Maison, Maison; Haryanto, Haryanto (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
The low quality and productivity of students' final assignments is a major challenge in higher education. This study aims to develop a collaborative supervision model through a multi-level approach to improve the quality and productivity of student research. The model encourages active collaboration among students, supervisors, and academic staff. Using an explanatory sequential mixed methods design, data were first collected quantitatively via questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM), followed by qualitative analysis using thematic analysis with NVIVO software. Bibliometric mapping was also carried out using VOSviewer to identify core concepts. Results show that the collaborative supervision model is valid and feasible according to expert validation. Field trials demonstrate a significant impact on increasing students’ independence, time management, motivation, and supervision effectiveness. This study provides a novel contribution by integrating individual, mentoring, and institutional levels in one comprehensive model, which has not been widely applied in traditional supervision practices. The findings imply that collaborative and structured academic supervision is crucial for developing high-quality student research outputs. The model developed can be a strategic alternative to enhance scientific literacy and academic productivity, especially in the context of science education, including physics education in higher education institutions.